Tribute to Lois Ehrenburg at Jon Jon's - Watkins, Howard::::::::: (1981)
James Vance Henry speaking at portable microphone; Margaret Sharp, Karen Humphrey, Dale Doig, Mary Nelson, Jim O'Banion watching